Phylogeny and biogeography of Bent-toed Geckos (Cyrtodactylus Gray) of the Sundaic swamp clade - Grismer, L. Lee; Davis, Hayden R. (Zootaxa, 2018)
The Sundaic swamp clade of the genus Cyrtodactylus contains nine species that collectively range through Peninsular Malaysia and its associated land bridge islands, Singapore, Sumatra, Java, and Pulau Natuna Besar. Ancestral range reconstruction analyses using BioGeoBEARS based on an updated molecular phylogeny of the nine Sundaic swamp clade species of Cyrtodactylus demonstrated that this lineage evolved in Peninsular Malaysia, dispersed independently to Sumatra and Pulau Natuna Besar, Indonesia and most likely back into Peninsular Malaysia from Sumatra. This scenario is consistent with climate-driven, cyclical, ephemeral, geographic reconfigurations of Sundaic landmasses from at least the mid-Miocene to present.